Establishment of primary cell cultures from fish calcified tissues - Marques, C. L. (2014)
Fishes have been recently recognized as a suitable model organism to study vertebrate physiological processes, in particular skeletal development and tissue mineralization. However, there is a lack of well characterized in vitro cell systems derived from fish calcified tissues. We describe here a protocol that was successfully used to develop the first calcified tissue-derived cell cultures of fish origin. Vertebra and branchial arches collected from young gilthead seabreams were fragmented then submitted to the combined action of collagenase and trypsin to efficiently release cells embedded in the collagenous extracellular matrix. Primary cultures were maintained under standard conditions and spontaneously transformed to form continuous cell lines suitable for studying mechanisms of tissue mineralization in seabream. This simple and inexpensive protocol is also applicable to other calcified tissues and species by adjusting parameters to each particular case.